Clinical correlates of HLA‐B*27 and its subtypes in enthesitis‐related arthritis variant of juvenile idiopathic arthritis in south Indian Tamil patients. (18th March 2019) - Kavadichanda, Chengappa G.; Seth, Gaurav; Kumar, Gunjan; Gulati, Reena; Negi, Vir Singh
Abstract: Aim: The aim of the study was to assess the distribution of human leukocyte antigen (HLA)‐B*27 subtypes and its correlation with disease phenotypes in children with enthesitis‐related arthritis variant of juvenile idiopathic arthritis (JIA‐ERA). Method: One hundred and sixty patients (132 males, 28 females) satisfying the International League Against Rheumatism (ILAR) classification criteria for JIA‐ERA were assessed and relevant demographic, clinical and radiographic data were documented. HLA‐B*27 typing was done for all the patients and B*27 positive samples were subjected to high‐resolution gene sequencing. The effect of duration of illness, HLA‐B*27, its subtypes, and gender on the clinical phenotype were analyzed. Results: The mean age of disease onset was 12.69 ± 2.4 years with a male:female ratio of 4.7:1.0. HLA‐B*27 was positive in 109/160 patients and HLA‐B*27:04 was detected in 63% followed by B*27:05 (30%). Duration of illness was greater in patients with skeletal deformity, hip arthritis, sacroiliitis, cervical spine involvement and acute anterior uveitis (AAU) ( P < 0.05). HLA‐B*27 positivity was associated with a prolonged course of disease, higher incidence of AAU (14.7% vs 2%, P = 0.015), family history of spondyloarthritis (21.1% vs 5.9%; P = 0.015) and higher erythrocyte sedimentation rate as compared to HLA‐B*27 negative patients ( P < 0.01). The HLA‐B*27:04 and *27:05 positive patients had similar clinical phenotypes. Conclusion: Presence of HLA‐B*27 and long duration of illness results in skeletal deformity, hip arthritis, sacroiliitis, cervical spine involvement and AAU. HLA‐B*27:04 followed by B*27:05 are the most common HLA‐B*27 subtypes in our study population and both have a similar clinical phenotype.